Analisis Regulasi Terhadap Pengembangan Industri Medical Tourism di Indonesia - Maria Chrisma Pramana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Indonesia still faces several challenges in developing medical tourism. Various sources, using data for 2018, show that Indonesian citizens actually go for treatment in Malaysia and Singapore, spending around US$23 billion, whether for treatment at government or private hospitals. The normative juridical method in this study will help in understanding the legal regulations and norms governing the medical tourism sector in the country, as well as assessing how these regulations affect the development of the industry. The results of this study are that Medical Tourism in Indonesia is regulated in Permenkes No.76/2015 concerning Health Tourism Services. PMK's weakness is the nuances of demand for the overseas patient market. Then the limitation that only type A and type B Hospitals are entitled to be designated as Hospitals with Medical Tourism Services in Indonesia is also an obstacle to the growth of the Health Tourism Service Climate. Not to mention, the socialization of the requirements for applying for a hospital for Health Tourism services is still lacking, including the requirements to be accredited (National Plenary level), and have cooperation documents with the Travel Bureau which has medical tour guides. To oversee the development of health tourism, the Indonesian Health Tourism Board (IHTB) was formed which was initiated by the Ministry of Maritime Affairs and Investment.